HPV Type Distribution in HIV Positive and Negative Women With or Without Cervical Dysplasia or Cancer in East Africa - Mcharo, Ruby; Lennemann, Tessa; France, John; Torres, Liseth; Garí, Mercè; Mbuya, Wilbert; Mwalongo, Wolfram; Mahenge, Anifrid; Bauer, Asli; Mnkai, Jonathan; Glasmeyer, Laura; Judick, Mona; et al. (Frontiers in Oncology, 2021)
Background Women living with HIV in sub-Saharan Africa are at increased risk to develop cervical cancer (CC), which is caused by persistent infection with thirteen oncogenic human papilloma viruses (HR-HPVs). It is important to accurately identify and target HIV positive women at highest risk to develop CC for early therapeutic intervention. Methods 2134 HIV+ and HIV- women from South-West Tanzania were prospectively screened for cervical cancer and precancerous lesions. Women with cervical cancer (n=236), high and low grade squamous intraepithelial lesions (HSIL: n=68, LSIL: n=74) and women without lesion (n=426) underwent high resolution HPV genotyping. Results 80% of women who were diagnosed with HSIL or LSIL were living with HIV. Any lesion, young age, HIV status and depleted CD4 T cell counts were independent risk factors for HPV infections, which were predominantly caused by HR HPV types. While multiple HR HPV type infections were predominant in HIV+ women with HSIL, single-type infections predominated in HIV+ CC cases (p=0.0006). HPV16, 18 and 45 accounted for 85% (68/80) and 75% (82/110) of HIV+ and HIV- CC cases, respectively. Of note, HPV35, the most frequent HPV type in HSIL positive women living with HIV, was rarely detected as a single-type infection in HSIL and cancer cases. Conclusion HPV16, 18 and 45 should receive special attention for molecular diagnostic algorithms during CC prevention programs for HIV+ women from sub-Saharan Africa. HPV35 may have a high potential to induce HSIL in women living with HIV, but less potential to cause cervical cancer in single-type infections.